Servant Leadership Styles: A Theoretical Approach - Thanh Nguyen Hai; Quang Nguyen Van (Ital Publication, 2021)
The main objective of the article is to examine the leadership style through a number of analyses, evaluations and researches from available sources, in order to discover suggested facts related to leadership activities through the prisms of servant leadership theory. So far, many leadership theories have been developed, proposing different leadership styles. One of the most discussed leadership styles is the servant leadership, which implies that a person must be human first, leader second. Every leader must whole heartedly serves an organization to which he/she belongs. This is both an honor and a great responsibility for the leader. The main methods used in the article are analysis, synthesis, evaluation based on literature review. The article aims to point out the outstanding strengths of the servant leadership style that a leader needs. The article focuses on specifying the strengths in servant leadership that leaders need in the current context of ever changing world, and hence, proposes guidelines for leaders to learn and practice so that they can better serve their public organizations. Doi: 10.28991/esj-2021-01273 Full Text: PDF